Proses Produksi Pembuatan Tekstur Material pada Desain 3d Karakter Menggunakan Perangkat Lunak Maxon 3D Bodypaint - Ardiyan Ardiyan (Humaniora, 2014)
Digital production proses using integrated image editor software, which has own drawing tools function, makes easier producing textures material that applied in 3D model. The feature of image editor combined with 3D Editor Software makes the easier adjustment of 3D model needs when we see the visible improvement, so the software utilization will be more efficient. In the discussion, this study is done by making the production of 3D model, that is the 3D Character that has material texturing from utilizing the available image editor software features, so the alternative production by using the integrated image editor is possibly to be done. The discussion can be utilized as an insight into the manufacture of technical design in determining the design workflow of 3D models. Utilization of software take one example of software Maxon Cinema 4D version 14, which is used as a reference as software that integrates image processing therein.